ENGLISH FOR HISTORY STUDENTS. Suport de curs pentru studenții de la specializarea Istorie, anul I - VOICHICI, Oana-Catalina (Presa Universitară Clujeană, 2017)
English language, one of the most widely spoken languages, is essential in the world of today. It is an important tool of communication; it gives students the opportunity of accessing English resources needed to progress in their studies; last, but not least, it may provide better job opportunities (sometimes, it is even an essential job requirement). This is why I believe that English language acquisition and the ability to use it are an absolute necessity. English for History Students is an exciting and informative book which addresses all students studying History (or those keen on approaching, more or less thoroughly, this constantly revealing field of knowledge). It is a language course intended to provide learners with basic historical facts about the United Kingdom and help them learn – and fix in their mind – English terms that are specific to this domain.